2004
DOI: 10.1186/1471-244x-4-25
|View full text |Cite
|
Sign up to set email alerts
|

The link between thyroid autoimmunity (antithyroid peroxidase autoantibodies) with anxiety and mood disorders in the community: a field of interest for public health in the future

Abstract: Background: To evaluate the association between mood and anxiety disorders and thyroid autoimmunity in a community sample. Methods: A community based sample of 222 subjects was examined. Psychiatric diagnoses were formulated using the International Composite Diagnostic Interview Simplified (CIDIS), according to DSM-IV criteria. All subjects underwent a complete thyroid evaluation including physical examination, thyroid echography and measure of serum free T4 (FT4), free T3 (FT3), thyroid-stimulating hormone (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 16 publications
9
86
1
4
Order By: Relevance
“…Recently, some investigators found a relation between thyroid auto-antibodies and mood and depression in subjects with a normal thyroid function (19,20). However, this is not confirmed by others (41), which is in line with our results.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recently, some investigators found a relation between thyroid auto-antibodies and mood and depression in subjects with a normal thyroid function (19,20). However, this is not confirmed by others (41), which is in line with our results.…”
Section: Discussionsupporting
confidence: 75%
“…A correlation between thyroid auto-antibodies and mood and depression has already been described by some authors (19,20). Other factors, however, that we are still unaware of could contribute to the reduction in QOL of our hypothyroid patients.…”
Section: Introductionmentioning
confidence: 86%
“…134 Taken together, studies of the HPT in MDD show evidence of altered activity of the HPT axis in some cases of depression, including (1) increased total and/or free T4, without T3 alterations; 128 (2) reduction in serum T4 concentration during a wide range of somatic treatments; 128,135 (3) increased TSH in 2-2.6% of patients; 125,129 (4) excessive response of TSH to the TRH challenge test in 10% and a blunted response in 25% of the patients; [135][136][137] and (5) high levels of antithyroid antibodies. 124,128,138,139 Some speculate that the mechanism of T4 increase with blunted TSH response to TRH reflects glucocorticoid activation of hypothalamic neurons. Bruhn et al 140 found that exposure of hypothalamic cultured fetal rats to glucocorticoids increased the genetic expression of TRH.…”
Section: Neuroendocrine Dysregulations In Patients With Mddmentioning
confidence: 99%
“…1 Carta and colleagues 1 are of the opinion that if these findings are confirmed in future, it may be advisable to systematically screen for mood disorders in patients with anti-thyroid peroxidase antibodies, and also evaluate for thyroid diseases and thyroid autoimmunity in patients with mood disorders. For now, it remains critical that clinicians have a high index of suspicion for mood disorders that may be secondary to a general medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 This prevalence, in concert with the suggested association between autoimmune thyroid disease and psychiatric disorders, makes it important to properly diagnose and treat this condition. The chronology of symptom presentation made it difficult to draw a conclusive association between our patient's mental disorder and her thyroid dysfunction.…”
Section: Discussionmentioning
confidence: 99%